Activation of Basolateral Amygdala to Nucleus Accumbens Projection Neurons Attenuates Chronic Corticosterone-Induced Behavioral Deficits in Male Mice - Dieterich, Andrew; Floeder, Joseph; Stech, Karina; Lee, Jay; Srivastava, Prachi; Barker, David J.; Samuels, Benjamin A. (Frontiers in Behavioral Neuroscience, 2021)
The basolateral amygdala (BLA) is critical for reward behaviors via a projection to the nucleus accumbens (NAc) (Beyeler et al., 2016). Specifically, BLA-NAc projections are involved in reinforcement learning, reward seeking, sustained instrumental responding, and risk behaviors (Stuber et al., 2011; Namburi et al., 2015; Namburi et al., 2016; Bercovici et al., 2018). However, it remains unclear whether chronic stress interacts with BLA-NAc projection neurons to result in maladaptive behaviors. Here we take a chemogenetic, projection-specific approach to clarify how NAc-projecting BLA neurons affect avoidance, reward, and feeding behaviors in male mice. Then, we examine whether chemogenetic activation of NAc-projecting BLA neurons attenuates the maladaptive effects of chronic corticosterone (CORT) administration on these behaviors. CORT mimics the behavioral and neural effects of chronic stress exposure (David et al., 2009; Dieterich et al., 2019). We found a nuanced role of BLA-NAc neurons in mediating reward behaviors. Surprisingly, activation of BLA-NAc projections rescues CORT-induced deficits in novelty suppressed feeding, a behavior typically associated with avoidance. Activation of BLA-NAc neurons also increases instrumental reward seeking without affecting free-feeding in chronic CORT mice. Taken together, these data suggest that NAc-projecting BLA neurons are involved in chronic CORT-induced maladaptive reward and motivation behaviors.